2018
DOI: 10.1186/s12916-018-1128-1
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain across continents and ethnicity: systematic review and meta-analysis of maternal and infant outcomes in more than one million women

Abstract: BackgroundThe association between Institute of Medicine (IOM) guidelines and pregnancy outcomes across ethnicities is uncertain. We evaluated the associations of gestational weight gain (GWG) outside 2009 IOM guidelines, with maternal and infant outcomes across the USA, western Europe and east Asia, with subgroup analyses in Asia. The aim was to explore ethnic differences in maternal prepregnancy body mass index (BMI), GWG and health outcomes across these regions.MethodsSystematic review, meta-analysis and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
352
3
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 357 publications
(390 citation statements)
references
References 59 publications
22
352
3
13
Order By: Relevance
“…With excessive GWG, mothers tend to have an increased risk of GDM, hypertensive disorders of pregnancy, cesarean section, postpartum weight retention, in addition to a lifelong risk of chronic diseases later on in life for the mother [64][65][66]. On the other hand, women gaining insufficient weight during their pregnancy are at an increased risk of delivering preterm birth and SGA [3,67]. Furthermore, accumulating evidence suggested that both excessive and insufficient GWG increase the risk for obesity and its associated cardiometabolic health consequences for the infant [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With excessive GWG, mothers tend to have an increased risk of GDM, hypertensive disorders of pregnancy, cesarean section, postpartum weight retention, in addition to a lifelong risk of chronic diseases later on in life for the mother [64][65][66]. On the other hand, women gaining insufficient weight during their pregnancy are at an increased risk of delivering preterm birth and SGA [3,67]. Furthermore, accumulating evidence suggested that both excessive and insufficient GWG increase the risk for obesity and its associated cardiometabolic health consequences for the infant [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis compiled data from one million pregnant women and reported a significant association between excessive GWG and increased risk of delivering a macrosomic and large for gestational age (LGA) babies. On the other hand, insufficient GWG was significantly associated with preterm delivery and small for gestational age (SGA) babies [3]. Such findings are alarming in light of the evidence linking both LGA and SGA with obesity and other chronic diseases later in life [4].…”
Section: Introductionmentioning
confidence: 99%
“…Taking the mean BMI of immigrant ethnic Chinese women with GDM in the present study as an example, the mean BMI of this cohort would be classified as overweight using Chinese BMI cut‐off points, yet is within the normal range when Caucasian cut‐off points are used. The importance of using ethnicity‐specific BMI cut‐off points in assessing pregnancy outcomes was highlighted in our recent international meta‐analysis . Clinicians should consider ethnicity‐specific BMI cut‐off points when identifying obesity as a risk factor for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of using ethnicity-specific BMI cut-off points in assessing pregnancy outcomes was highlighted in our recent international metaanalysis. 39 Clinicians should consider ethnicity-specific BMI cut-off points when identifying obesity as a risk factor for GDM. Abbreviations: BMI, body mass index; PCOS, polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Частота его возникновения в разных странах мира составляет 1-8,6%, и каждые 10-15 лет число больных СД увеличивается в 2 раза [1][2][3][4][5][6][7]. Большинство клиницистов [8][9][10][11][12][13] считают сахарный диабет медико-социальной проблемой. Среди всех эндокринных заболеваний СД оказывает наиболее неблагоприятное влияние на течение беременности, приводя к осложнениям, отрицательно воздействуя на внутриутробное развитие плода и адаптационные возможности новорожденного.…”
unclassified